Guru Pendidikan Islam Dalam Konsep 5M - Rahmad Fauzi Lubis (LPPM STAI Diniyah Pekanbaru, 2020)
Research in the concept aims to see Islamic education teachers in the 5M concept and the opinions of Islamic education experts in a concept that is able to deliver a teacher to become a role model in order to achieve educational goals. This research is qualitative research. Much memorable Islamic education has to do with the teacher. Smart teachers will produce smart students, the foundation for the development of Islamic education teachers itself is important to produce a memorable educator. In this study, we will discuss the characteristics of Islamic education teachers based on the 5M concept.